Sustainable land management of apple replant sites of Himachal Pradesh - Sharma, Ranjna (Indian Horticulture, 2024)
Apple replant problem is a major issue in all apple growing areas of world including India. Due to small land holdings and difficult land terrain in Himachal Pradesh, it is impossible for apple orchardists to shift the plantation sites. Most of the apple orchards have completed their life span (40-50 years old) and these old orchard sites when replanted with the same crop, farmers face a lot of problems in terms of establishment of new plantation, poor growth, and sensitivity towards different soil borne pathogens and reduction in fruit yield. The main causes are soil pathogenic fungi, nematodes, nutrient exhaustion/loss, pH imbalances, heavy metal contamination and toxic root exudates of old apple trees. Chemical pesticides are used against soil pathogenic microbes but they sometimes target the plant beneficial microbes. Therefore, use of integrated sustainable land management strategies which are economical, environment friendly both to the plants and human beings are discussed in the present article to overcome the apple replant issue.